Closure of pulmonary arterio-venous malformations in a patient with a novel form of Hereditary Haemorrhagic Telangiectasia - Weich, Hellmuth; Ackermann, Christelle (SA Heart Journal, 2017)
Hereditary Haemorrhagic Telangiectasia.